Strategi Pemerintah Terhadap Pemungutan Pajak Di Indonesia - Saputri, Berliana Ayu (Universitas Widya Gama Malang, 2024)
This study aims to analyze the obstacles that occur in tax collection and the government's strategy in dealing with obstacles to tax collection in Indonesia and the implementation of taxes in Indonesia. This journal uses normative legal research methods or doctrinal research. The sources of legal materials used are primary legal materials and secondary legal materials. The procedure for collecting legal materials in this journal is by studying documents or library materials. Analysis of legal material sources is carried out descriptively using a statutory approach and a contextual approach. The results of the study concluded that the tax collection application system that is known in Indonesia consists of several things, namely: Official Assessment system, semi self assessment system, full self assessment system and witbbbolding. Obstacles in tax collection, namely passive tax resistance consisting of obstacles that complicate tax collection which are closely related to the economic structure, intellectual and moral development of the population and active resistance are efforts or actions that are directly or indirectly shown against tax collection. tax (Fiskus). As for the strategy carried out by the Directorate General of Taxes, the government needs to take a territorial approach to carry out tax extensions. tax extensification is supervision carried out by the Directorate General of Taxes on taxpayers who meet subjective and objective requirements but do not yet have a Taxpayer Identification Number and promote counseling in the field of taxation.